Liberalisasi di Inggris, 1970-1990 - Ahmad Hanafi (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
Under Margareth Tarcher leadership in 1970-an, Great Brittain lead a global process of transforming the role of the state in governing the econmy. The attempt to leaved the old framework of Keynesian welfare state and embarking on neoliberal terrain inevitably brought about the changing of class structure and marginalise the labour in order to gain international advantage.